Modeling Traditional Gobak Sodor Games Through a Play Approach to Improve Physical Fitness of Grade V Students of SDN 1 Rantebua - Tia; Irsan Kahar; Syamsul Alam Ramli (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
This study aims to improve children's physical fitness in the traditional game of gobak sodor. The method used in this study used a pre-experimental research method with a single group pretest - posttest research design (The One Group Pretest Posttest Design) with a sample of 30 SDN 1 Rantebua students. The data collection technique used was carried out using the Physical Fitness Test. The results of this study indicate that the average value (mean) of the pretest is 59.73 and the posttest is 69.00 Std.Deviation pretest 5.819 and posttest 5.318. minimum value pretest 50 and posttest 60. The maximum value pretest 68 and posttest 75. Then the probability number of sig is 0.000>0.05 which means Ho is rejected. Thus it can be concluded that there is a significant effect on increasing physical fitness in class students of SDN 1 Rantebua which means that the traditional game model program gobak sodor through a play approach to improve the physical fitness of SDN 1 rantebua class students can improve physical fitness in students.